The Smoking Paradox in Stroke Patients Under Reperfusion Treatment Is Associated With Endothelial Dysfunction - Iglesias-Rey, Ramón; Custodia, Antía; Alonso-Alonso, Maria Luz; López-Dequidt, Iria; Rodríguez-Yáñez, Manuel; Pumar, José M.; Castillo, José; Sobrino, Tomás; Campos, Francisco; Silva-Candal, Andres da; Hervella, Pablo (Frontiers in Neurology, 2022)
Objective: To study the association between smoking habit and the serum levels of soluble tumor necrosis factor-like weak inducer of apoptosis (sTWEAK), in relation with the functional outcome of patients with acute ischemic stroke undergoing reperfusion treatment. Methods: Observational and retrospective study of a series of patients with acute ischemic stroke subjected to reperfusion treatments. Clinical, analytical and neuroimaging parameters were analyzed. The main endpoint was the functional outcome at three months, measured by the mRS. Logistic regression models were used to analyze the association between smoking and sTWEAK levels with functional outcome and leukoaraiosis. Results: Smoking habit was associated with good functional outcome at 3 months in stroke patients (OR: 3.52; CI 95%: 1.03–11.90; p=0.044). However, this independent association was lost after adjusting by sTWEAK levels (OR 1.73; CI 95%: 0.86 - 13.28; p=0.116). sTWEAK levels were significantly lower in smoker patients (4015.50 [973.66 - 7921.83] pg/mL vs. 5628 [2848-10202] pg/mL, p<0.0001), while sTWEAK levels were significantly higher in patients with poor functional outcome at 3 months (10284 [7388-13247] pg/mL vs. 3405 [2329- 6629] pg/mL, p<0.0001). Conclusion: The decrease in sTWEAK levels is associated with the good functional outcome in smoking stroke patients undergoing reperfusion therapy.